Helicobacter pylori infection in family members of patients with gastroduodenal symptoms. A cross-sectional analytical study - Palanduz, Ayse; Erdem, Levent; Cetin, Birsen Durmaz; Ozcan, Nuran Gülgün (São Paulo Medical Journal, 2018)
BACKGROUND: Primary Helicobacter pylori (H. pylori) infection is acquired predominantly in childhood in the family setting. We aimed to investigate the presence of intrafamilial concurrent H. pylori infection. DESIGN AND SETTING: Cross-sectional analytical study with a control group, conducted in a tertiary care hospital. METHODS: Fifty adult patients with gastroduodenal symptoms who underwent gastroscopy (index parents), their spouses and their children were enrolled in the study. Blood samples were collected from all of the study subjects to test for immunoglobulin G (IgG) antibody response. H. pylori antigen was investigated in the stool specimens of children only. RESULTS: The participants were divided into two groups: Group 1 consisted of the 40 patients in whom H. pylori infection was demonstrated via endoscopy, their spouses and their children. Group 2 included the remaining 10 patients who underwent endoscopy revealing negative results for H. pylori, their spouses and their children. IgG antibodies were present in all of the index parents, 95% of their spouses and 93% of their children in group 1; 13 of the children (9%) were also positive for H. pylori stool antigen (HpSA). However, IgG antibodies were present in only 2 of the 10 index parents in group 2. One of their spouses and one of their children had a positive antibody response. All of their children had negative stool antigen test results. CONCLUSION: H. pylori infections exhibit intrafamilial clustering. Parental infection, age ≥ 7 years and having three or more siblings are the major risk factors for H. pylori infection in children.